Scaling Up Affordable Health Insurance : Staying the Course - Preker, Alexander S.; Lindner, Marianne E.; Chernichovsky, Dov; Schellekens, Onno P. (Washington, DC: World Bank, 2013)
As the world recently turned its attention to the struggle of expanding health insurance coverage for 40 million people in the United States, it is important not to forget the 4 billion people in low- and middle-income countries that face the same hardship. Millions of the poor have already fallen back into poverty as a result of the ongoing global financial crisis. Millions more are at risk before full recovery. It is the poor and most vulnerable that are at greatest risk due to lack of protection against the impoverishing effects of illness. The research for this volume shows that, when properly designed and coupled with public subsidies, health insurance can contribute to the well-being of poor and middle-class households, not just the rich. And it can contribute to development goals such as improved access to health care, better financial protection against the cost of illness, and reduced social exclusion. Opponents vilify health insurance as an evil to be avoided at all cost. To them, health insurance leads to overconsumption of care, escalating costs-especially administrative costs-fraud and abuse, shunting of scarce resources away from the poor, cream skimming, adverse selection, moral hazard, and an inequitable health care system. Today many low-and middle-income countries are no longer listening to this dichotomized debate between vertical and horizontal approaches to health care. Instead, they are experimenting with new and innovative approaches to health care financing. Health insurance is becoming a new paradigm for reaching the Millennium Development Goals (MDGs). They emphasize the need to combine several instruments to achieve three major development objectives in health care financing: 1) sustainable access to needed health care; 2) greater financial protection against the impoverishing cost of illness; and 3) reduction in social exclusion from organized health financing instruments. The use of insurance was recommended to pay for less frequent, higher-cost risks and subsidies to cover affordability for poorer patients to higher-frequency, lower-cost health problems.